2012
DOI: 10.1007/s00436-012-3025-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of imidacloprid 10 %/moxidectin 1 % spot-on formulation in the treatment of feline infection by Capillaria aerophila

Abstract: The nematode Capillaria aerophila (Trichuroidea, Trichuridae) affects the respiratory system of cats and other animals and occasionally of human beings. Infected cats may show bronchovesicular sounds, inflammation, sneezing, wheezing and, chronic cough and, sometimes, bronchopneumonia and respiratory failure. The present study evaluated the efficacy and safety of the antiparasitic spot-on formulation containing imidacloprid 10 %/moxidectin 1 % (Advocate®, Bayer Animal Health) in the treatment of natural feline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
(21 reference statements)
2
39
0
1
Order By: Relevance
“…It was found in European wildcats from Germany (Krone et al 2008) and southern Italy (Falsone et al 2014) and northern Italy (Beraldo et al 2014). The absence of C. aerophila in most cats from areas where prevalence of capillarids in domestic carnivores is high (Traversa et al 2009(Traversa et al , 2012Di Cesare et al 2011;Veronesi et al 2013Veronesi et al , 2014a suggests that the European wildcat is not a primary host for C. aerophila. However, F. s. silvestris can harbor this parasite, although other wildlife such as foxes and mustelids may play a primary role in the epizootiology of lung capillariosis .…”
Section: Discussionmentioning
confidence: 99%
“…It was found in European wildcats from Germany (Krone et al 2008) and southern Italy (Falsone et al 2014) and northern Italy (Beraldo et al 2014). The absence of C. aerophila in most cats from areas where prevalence of capillarids in domestic carnivores is high (Traversa et al 2009(Traversa et al , 2012Di Cesare et al 2011;Veronesi et al 2013Veronesi et al , 2014a suggests that the European wildcat is not a primary host for C. aerophila. However, F. s. silvestris can harbor this parasite, although other wildlife such as foxes and mustelids may play a primary role in the epizootiology of lung capillariosis .…”
Section: Discussionmentioning
confidence: 99%
“…90 The safety and efficacy of the topical combination containing eprinomectin (Broadline) was evaluated against helminths, including Capillaria species, in domestic cats. An efficacy of 99.6% in reducing counts of Capillaria eggs was reported after treatment.…”
Section: Aerophilamentioning
confidence: 99%
“…Data obtained in this study confirm previous findings on the efficacy of moxidectin in the treatment of C. aerophila in cats. In fact, a recent study showed a 99.79 % reduction of C. aerophila egg counts in Advocate ® -treated animals in comparison with cats left untreated (Traversa et al 2012). In summary, this information is of high interest from a clinical viewpoint considering that no drugs are currently marketed with C. aerophila as an indication for use in cats and that, in general, information on the field efficacy of parasiticides in the treatment of pulmonary capillariosis in cats is poor.…”
Section: Discussionmentioning
confidence: 96%
“…Advocate ® (Bayer) is a spot-on formulation containing the macrocyclic lactone endectocide moxidectin 1 % (w/v) and the neonicotinoid insecticide imidacloprid 10 % (w/v) that is currently approved in Europe for the treatment of a wide range of ectoparasites and endoparasites of cats. A Good Clinical Practice (GCP) study carried out from 2009 -2011 demonstrated the efficacy and safety of Advocate ® in the treatment of cat capillariosis (Traversa et al 2012). This article describes a second GCP trial that has been performed to further evaluate the therapeutic efficacy and safety of Advocate ® in cats naturally infected with C. aerophila.…”
Section: Introductionmentioning
confidence: 99%